2005
DOI: 10.1097/00003072-200503000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Honda Sign and Variants in Patients Suspected of Having a Sacral Insufficiency Fracture

Abstract: A "Honda sign or variation" with evidence of fractures elsewhere or no evidence of other metastatic disease should be strong evidence for a sacral insufficiency fracture. The likelihood of having a solitary metastasis to the sacrum is small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 10 publications
1
49
1
6
Order By: Relevance
“…4,31 Variations in the pattern of radiopharmaceutical activity in SIFs include uptake oriented unilaterally in the sacral ala, unilaterally with a horizontal strut, bilaterally without a horizontal strut, and as multiple foci of activity. 34 Posterior planar images are the most sensitive (ie, when the sacrum is closest to the detector). 29 Follow-up scintigraphic results are quite variable, with changes in the radiopharmaceutical uptake pattern during a 10-to 33-month interval, ranging from resolution of abnormal activity to no change or even worsening activity.…”
Section: Nuclear Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…4,31 Variations in the pattern of radiopharmaceutical activity in SIFs include uptake oriented unilaterally in the sacral ala, unilaterally with a horizontal strut, bilaterally without a horizontal strut, and as multiple foci of activity. 34 Posterior planar images are the most sensitive (ie, when the sacrum is closest to the detector). 29 Follow-up scintigraphic results are quite variable, with changes in the radiopharmaceutical uptake pattern during a 10-to 33-month interval, ranging from resolution of abnormal activity to no change or even worsening activity.…”
Section: Nuclear Medicinementioning
confidence: 99%
“…3,9,22,31 Bone scintigraphy has a reported sensitivity of 96% for the detection of SIFs, with a positive predictive value of 92%. 34 Some authors have suggested that characteristic patterns of uptake in the sacrum should be considered diagnostic in the correct clinical context, especially if there are no other sites of abnormal activity in the skeleton and no history of primary malignancy. 33 However, there have been case reports of isolated metastases presenting as unilateral sacral uptake.…”
Section: Nuclear Medicinementioning
confidence: 99%
“…The typical so-called ''Honda'' sign or H-pattern is considered diagnostic of SIF, however it is visible in only up to 40% of cases [10]. Bone scan has a reported sensitivity of 96% for the detection of SIFs [11]. However it might be difficult to differentiate between benign and malignant bone lesions with planar bone scan alone.…”
Section: Discussionmentioning
confidence: 99%
“…Some patterns of uptake, such as the BHonda signf or sacral insufficiency fractures can be diagnostic, with sensitivity and positive predictive value of up to 96 and 92 %, respectively (Fig. 5) [52,53].…”
Section: Imagingmentioning
confidence: 99%